The Role of Health Workers and Community Leaders to Prevent Dengue Hemorrhagic Fever in Magetan, East Java - Dimas Abdullah Marha; Mohammad Zainal Fatah; Winarko Winarko (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2020)
ABSTRACTBackground: Dengue Hemorrhagic Fever (DHF) is still one of the major public health problems in Indonesia. With the increasing mobility and population density, the number of people and vast distribution area is increasing. Village of Tawanganom is one endemic region, for three consecutive years, there is an incidence of dengue. The incidence of dengue can be influenced by several aspects, including vectors, climate change, environment, mobility of people, and people's behavior. The participation of health workers and community leaders become important related behavior. These include the role of motivation, coordination, policy implementation, as well as healthy behaviors. Objective: This study aimed to determine the role of health workers and community leaders in response to the incidence of dengue in the Village Tawanganom. Methods: Using qualitative research with a phenomenological approach, as well as in-depth interviews carried out with supporting data, the number of informants were 13 informants. Consisting of health professionals that the holder of dengue program, Health Promotor, and village midwives, community leaders the Head of the village, RW, as well as health cadres. Results: The motivation of public figures came from the concern over them because of the many cases of DHF and personal experiences of informants and families. Health workers motivate people to do counseling, which was supported because of responsibility as health professionals. Coordination has been made with the relevant sectors. Reporting cases of executed massively and focused. Implementation of policies in the prevention of dengue fever has been carried out based dengue prevention program Magetan District Health Office. Healthy behavior is shown with dengue prevention measures such as 3M Plus, giving abate powder in the bathroom, as well as maintaining the cleanliness of the home environment. Conclusion: The motivation to do a public figure driven intrinsic motivation of the individuals themselves, while medical personnel with extrinsic motivation based on the responsibility as health workers to encourage people to do the prevention of dengue. Coordination has been carried out massively and regularly within the scope of cross-fertilization. Implementation of policies based on the program of the Health Service Magetan. Healthy behavior implemented preventive and promotive measures.